How Do Local Folks Value Wild Meat, and Why It Matters? A Study in the Eastern Democratic Republic of Congo - Vliet, N. van; Nyumu, J.K.; Nziavake, S.; Muhindo, J.; Paemelaere, E.A.D.; Nasi, R. (Springer, 2022)
We elucidate the value orientations (VOs) towards wild meat/wildlife in the Tshopo Province of the Democratic Republic of Congo, distinguishing between the provincial capital and rural areas. Based on stories prompted by four primary emotions, the most frequently encountered VOs were: concern for safety, nutrition and taste, and caring/respect. Rural people were more likely to express anthropocentric VOs. However, their stories did not necessarily associate negatively with caring/respect, suggesting that wildlife users may also be sensitive to biocentric values. Age, gender, and wealth were good predictors for biocentric VOs, with young women from the city more likely to express biocentric values. VOs and emotions related differently to specific wildlife species. Mutualism was not frequently elucidated in the stories. The associations we found provide crucial information to understand differences in value orientations across groups, identify barriers to change, and tailor behavior change campaigns to the local context.